Fairy tale as myth/myth as fairy tale - Zipes, Jack, 1937- (Lexington : University Press of Kentucky, 1994)
Traces the history of the fairy tale genre from its rise in the late seventeenth century to its role in modern life, focusing on key classic fairy tales and what they reveal about domination and oppression in Western society.
Includes bibliographical references (p. [162]-185) and index.
Adult.
Adult
Keywords: Fairy tales -- Classification; Fairy tales -- History and criticism; Fairy tales -- Classification; Fairy tales -- History and criticism